Cell membrane-camouflaged nanoparticles as drug carriers for cancer therapy - Xu, Cheng-Hui; Ye, Peng-Ju; Zhou, Yang-Chun; He, Dong-Xiu; Wei, Hua; Yu, Cui-Yun (Acta biomaterialia, 2020)
The translocation of natural cell membranes to the surface of synthetic nanoparticles, which allows man-made vectors to share merits and functionalities created by nature, has been a hot subject of research in the past decade. The resulting biomimetic nanoparticles not only retain the physicochemical properties of nanomaterials, but also inherit the advantageous functions of source cells. Combined with the preponderances of both synthetic and natural platforms, the optimized biomimetic systems can maximize the drug delivery efficiency. In this review, we first summarize the preparation strategies of the biomimetic systems from the perspective of the correlation between the properties of nanoparticles and cell membranes. Six types of cell membrane-camouflaged nanoparticles are further introduced with an emphasis on their properties and performance. Finally, a concluding remark regarding the primary challenges and opportunities associated with these nanoparticles is presented. Translocation of natural cell membranes to the surface of synthetic nanoparticles has been repeatedly highlighted in the past decade to endow man-made vectors with merits and functionalities created by nature; therefore, the resulting biomimetic systems not only retain the physicochemical properties of nanomaterials but also inherit the biological functions of source cells for efficient drug delivery. To provide a timely review on this hot and rapidly developing subject of research, this paper summarized recent progress on the cell membrane-camouflaged nanoparticles as drug carriers for cancer therapy, and focused primarily on six different types of cell membrane-coated nanoparticles with an emphasis on the preparation strategies from the perspective of the correlation between the properties of nanoparticles and cell membrane. [Display omitted]